Kiai Leadership in Advancing Agribusiness Enterprises in Islamic Boarding Schools in Jambi Province - Nurusydiyati; Kasful Anwar; Lukman Hakim; Ethan J. Callahan (International Journal of Post Axial: Futuristic Teaching and Learning, 2025)
This study explores the role of kiai leadership in the development of agribusiness enterprises at Islamic boarding schools (pesantren) in Jambi Province. The research was conducted at three pesantren: Raudhatul Mujawwidin in Tebo Regency, Irsyadul Ibad in Batanghari Regency, and Al Muttaqin in Muaro Jambi Regency. These institutions were selected due to their active involvement in agribusiness as part of pesantren-based economic empowerment efforts. The study reveals that the leadership of the kiai plays a central role in initiating, managing, and sustaining agribusiness activities. Their leadership is not only spiritual and educational, but also entrepreneurial, as they mobilize resources, inspire the santri and surrounding communities, and establish strategic collaborations with external partners. The success of agribusiness development in these pesantren is closely linked to the kiai’s visionary leadership, adaptability, and commitment to the values of independence and community welfare. This research highlights the importance of integrating religious leadership with entrepreneurial skills to strengthen the economic sustainability of Islamic educational institutions.